COVID-19 related immunization disruptions in Rajasthan, India: A retrospective observational study. Issue 31 (13th July 2021) - Jain, Radhika; Chopra, Ambika; Falézan, Camille; Patel, Mustufa; Dupas, Pascaline
Highlights: Disruptions during the COVID-19 lockdown caused children to miss immunizations. Government catch-up efforts substantially reversed these effects. Yet, children that were due vaccinations during the lockdown remained 10–15% less likely to be immunized 4–5 months later. Catch-up was more likely to be incomplete among children of low socioeconomic status. Ensuring all children are fully immunized requires careful tracking and disaggregated data. Abstract: Introduction: Governments around the world suspended immunization outreach to control COVID-19 spread. Many have since resumed services with an emphasis on catch-up vaccinations. This paper evaluated immunization disruptions during India's March-May 2020 lockdown and the extent to which subsequent catch-up efforts reversed them in Rajasthan, India. Methods: In this retrospective observational study, we conducted phone surveys to collect immunization details for 2, 144 children that turned one year old between January and October 2020. We used logistic regressions to compare differences in immunization timeliness and completed first-year immunization status among children that were due immunizations just before (unexposed), during (heavily exposed), and after (post-exposure) the lockdown. Results: Relative to unexposed children, heavily exposed children were significantly less likely to be immunized at or before 9 months (OR 0.550; 95% CI 0.367–0.824; p = 0.004), but more likely to be immunized at 10–12 months (OR 1.761; 95% CI 1.196–2.591; p = 0.004). They were also less likely to have completed their key first-year immunizations (OR 0.624; 95% CI 0.478–0.816; p = 0.001) by the time of survey. In contrast, post-exposure children showed no difference in timeliness or completed first-year immunizations relative to unexposed children, despite their younger age. First-year immunization coverage among heavily exposed children decreased by 6.9 pp to 10.4 pp (9.7% to 14.0%). Declines in immunization coverage were larger among children in households that were poorer, less educated, lower caste, and residing in COVID red zones, although subgroup comparisons were not statistically significant. Conclusion: Disruptions to immunization services resulted in children missing immunization during the lockdown, but catch-up efforts after it was eased ensured many children were reached at later ages. Nevertheless, catch-up was incomplete and children due their immunizations during the lockdown remained less likely to be fully immunized 4–5 months after it lifted, even as younger cohorts due immunizations in June or later returned to pre-lockdown schedules.